Capsaicin Supplementation during High-intensity Continuous Exercise: A Double-blind Study - Padilha, Camila S. [UNESP]; Billaut, Francois; Figueiredo, Caique [UNESP]; Panissa, Valéria Leme Gonçalves; Rossi, Fabrício Eduardo; Lira, Fabio S. [UNESP] (Thieme, 2020)
To investigate the effect of acute capsaicin (CAP) supplementation on time to exhaustion, physiological responses and energy systems contribution during continuous high-intensity exercise session in runners. Fifteen recreationally-Trained runners completed two randomized, double-blind continuous high-intensity exercises at the speed eliciting 90% VO 2peak(90% s VO 2peak), 45 minutes after consuming capsaicin or an isocaloric placebo. Time to exhaustion, blood lactate concentration, oxygen consumption during and 20-min post-exercise, energy systems contribution, time to reach VO 2peak, heart rate and the rate of perceived exertion (RPE) were evaluated. There was no significant difference between conditions for time to reach VO 2peak(CAP:391.71±221.8 vs. PLA:298.20±174.5 sec, ES:0.58, p=0.872), peak lactate (CAP:7.98±2.11 vs. PLA:8.58±2.15 μmol, ES:-0.28, p=0.257), time to exhaustion (CAP:654.28±195.44 vs. PLA:709.20±208.44 sec, ES:-0.28, p=0.462, end-of-exercise heart rate (CAP:177.6±14.9 vs. PLA:177.5±17.9 bpm, ES:-0.10, p=0.979) and end-of-exercise RPE (CAP: 19±0.8 vs. PLA: 18±2.4, ES: 0.89, p=0.623). In conclusion, acute CAP supplementation did not increase time to exhaustion during high-intensity continuous exercise nor alter physiological responses in runners
Keywords: anaerobic energy; capsaicin; continuous protocol; excess of post-exercise oxygen consumption; lactate; muscle fatigue